The tale of Kitty-in-Boots - Potter, Beatrix, 1866-1943; Blake, Quentin (New York, New York, USA : F. Warne & Co., 2016)
A young black cat gets more of an adventure than she bargained for when she goes from predator to prey on a hunting trip.
Keywords: Cats -- Fiction; Animals -- Fiction; Hunting -- Fiction; Cats -- Fiction; Animals -- Fiction; Hunting -- Fiction